Postprandial triglycerides and adipose tissue storage of dietary fatty acids: Impact of menopause and estradiol. (30th October 2014) - Bessesen, Daniel H.; Cox‐York, Kimberly A.; Hernandez, Teri Lynn; Erickson, Christopher B.; Wang, Hong; Jackman, Matt R.; Van Pelt, Rachael E.
<x xml:space="preserve">Abstract</x> Objectives Postprandial lipemia worsens after menopause, but the mechanism remains unknown. The hypothesized menopause‐related postprandial lipemia would be (1) associated with reduced storage of dietary fatty acids (FA) as triglyceride (TG) in subcutaneous adipose tissue (SAT) and (2) improved by short‐term estradiol (E2). Methods Twenty‐three pre‐ (mean ± SD: 42 ± 4 years) and 22 postmenopausal (55 ± 4 years) women with similar total adiposity were studied. A subset of postmenopausal women (n = 12) were studied following 2 weeks of E2 (0.15 mg) and matching placebo in a random, cross‐over design. A liquid meal containing 14C‐oleic acid traced appearance of dietary FA in: serum (postprandial TG), breath (oxidation), and abdominal and femoral SAT (TG storage). Results Compared to premenopausal women, healthy, lean, postmenopausal women had increased postprandial glucose and insulin and trend for higher TG but had similar dietary FA oxidation and storage. Adipocytes were larger in post‐ compared to premenopausal women, particularly in femoral SAT. Short‐term E2 reduced postprandial TG and insulin but had no effect on oxidation or storage of dietary FA. E2 increased the proportion of small adipocytes in femoral (but not abdominal) SAT. Conclusions Short‐term E2 attenuated menopause‐related increases in postprandial TG and increased femoral adipocyte hyperplasia but not through increased net storage of dietary FA.